Color changes, EMC, and biological resistance of thermally modified yellow poplar - Brito, A. F. [UNESP]; Calonego, F. W. [UNESP]; Bond, B. H.; Severo, E. T.D. [UNESP] (My University, 2018)
Liriodendron tulipifera L., known as yellow poplar, are fast-growing trees, make up about 17% of commercially available hardwood in North America, and are generally used in furniture, doors, and millwork. The wood is used mostly where it would be hidden or painted. The value of yellow poplar is less than that of other hardwoods with more pronounced grain and color. This study evaluated the effect of various levels of thermal treatment on color and resistance to decay fungus and termites of yellow poplar wood. Boards (28.57 mm thickness 150 mm width 3.65 m length) were taken from a sawmill and thermally modified at temperatures of 180°C, 200°C, and 220°C. A summary of the findings were that thermal treatment caused: 1) darkening and reddening of yellow poplar wood; 2) a reduction of up to 51.4% in EMC when exposed to 21°C and 65% relative humidity, and 3) a significant increase in wood decay resistance against decay fungus Pycnoporus sanguineus. Treatment at 220°C resulted in a change in American Society of Testing Materialswood decay resistance class from slightly resistant to highly resistant; and no significant changes in resistance against the dry-wood termites Cryptotermes brevis were found.
Keywords: Colorimetric values; Cryptoermes brevis; Liriodendron tulipifera; Pycnoporus sanguineus; Thermal modification